Characterization of the precursor of Serratia marcescens serine protease and COOH-terminal processing of the precursor during its excretion through the outer membrane of Escherichia coli. - Miyazaki, H (1989)
The Serratia marcescens serine protease, which is directed by the gene encoding a precursor composed of a typical NH2-terminal signal sequence, a mature enzyme domain, and a large COOH-terminal domain, was excreted through the outer membrane of Escherichia coli. The precursor, with the expected molecular size (110 kilodaltons), was detected in an insoluble form in the periplasmic space of E. coli cells after induction with isopropyl-beta-D-thiogalactopyranoside of the expression of the gene under the control of the tac promoter. Upon membrane fractionation of the disrupted cells by sucrose density gradient centrifugation, the precursor was recovered from a fraction slightly heavier than the outer membrane fraction but not from the inner membrane fraction. Conversion of the precursor into the mature form, which was accompanied by its excretion into the medium, was observed even in the absence of de novo protein synthesis caused by the addition of chloramphenicol. The mutated gene product lacking all of the COOH-terminal domain was localized in the periplasmic space only and was not excreted into the medium. Additional mutant genes were generated by site-directed mutagenesis to test the role of some amino acids in the excretion of this protease in E. coli. The mutant protein with no protease activity because of the change of the catalytic residue Ser-341 to Thr was still excreted into the medium but with abnormal processing. Both self-processing and host-dependent processing of the precursor seem to be involved in the excretion of the mature enzyme. Replacement of the four Cys residues, two in the mature enzyme and two in the COOH-terminal domain, with Ser in different combinations caused a distinct or complete loss of excretion, suggesting that a certain conformation possibly formed via disulfide bonding was important for the excretion of the S. marcescens protease.